Kinetics of Fluorescein in Tear Film After Eye Drop Instillation in Beagle Dogs: Does Size Really Matter? - Sebbag, Lionel; Kirner, Nicolette S.; Allbaugh, Rachel A.; Reis, Alysha; Mochel, Jonathan P. (Frontiers in Veterinary Science, 2019)
The study aimed to determine the impact of drop size on tear film pharmacokinetics and assess important physiological parameters associated with ocular drug delivery in dogs. Two separate experiments were conducted in eight healthy Beagle dogs: (i) Instillation of one drop (35 μl) or two drops (70 μl) of 1% fluorescein solution in each eye followed by tear collections with capillary tubes from 0 to 180 min; (ii) Instillation of 10 to 100 μl of 0.1% fluorescein in each eye followed by external photography with blue excitation filter (to capture periocular spillage of fluorescein) and tear collections from 1 to 20 min (to capture tear turnover rate; TTR). Fluorescein concentrations were measured in tear samples with a fluorophotometer. The TTR was estimated based upon non-linear mixed-effects analysis of fluorescein decay curves. Tear film pharmacokinetics were not superior with instillation of two drops vs. one drop based on tear film concentrations, residual tear fluorescence, and area under the fluorescein-time curves (P ≥ 0.163). Reflex TTR varied from 20.2 to 30.5%/min and did not differ significantly (P = 0.935) among volumes instilled (10–100 μl). The volumetric capacity of the canine palpebral fissure (31.3 ± 8.9 μl) was positively correlated with the palpebral fissure length (P = 0.023). Excess solution was spilled over the periocular skin in a volume-dependent manner, predominantly in the lower eyelid, medial canthus and lateral canthus. In sum, a single drop is sufficient for topical administration in dogs. Any excess is lost predominantly by spillage over the periocular skin as well as accelerated nasolacrimal drainage.